2012
DOI: 10.2174/092986712800229069
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Agents from Plants: Progress and Potential

Abstract: The identification of substances that can promote the resolution of inflammation in a way that is homeostatic, modulatory, efficient, and well-tolerated by the body is of fundamental importance. Traditional medicines have long provided front-line pharmacotherapy for many millions of people worldwide. Medicinal extracts are a rich source of therapeutic leads for the pharmaceutical industry. The use of medicinal plant therapies to treat chronic illness, including rheumatoid arthritis (RA) and inflammatory bowel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(49 citation statements)
references
References 112 publications
(141 reference statements)
1
48
0
Order By: Relevance
“…Plant products have been used in traditional medicine for many years, and their anti-inflammatory, anti-allergic and anti-infective properties are well-established [1113]. Recent reports have indicated that these natural compounds also have angiogenesis-modulating effects [14–16].…”
Section: Introductionmentioning
confidence: 99%
“…Plant products have been used in traditional medicine for many years, and their anti-inflammatory, anti-allergic and anti-infective properties are well-established [1113]. Recent reports have indicated that these natural compounds also have angiogenesis-modulating effects [14–16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, resveratrol has gained considerable attention due to its anticancer (38), cardiovascular protective (39) and anti-inflammatory effects (40). A previous study has shown that resveratrol can effectively reduce mRNA levels of major proinflammatory cytokines (IL-6 and IL-8), TLR2, and matrix degrading enzymes (MMP1, MMP3 and MMP13) (41), which have previously been shown to be involved in disc degeneration and pain induction (42).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol (trans-3,4,5-trihydroxystillbene) is a polyphenol naturally found in various plant species (Recio et al, 2012). The use of resveratrol in treating various inflammatory diseases has been studied extensively due to its anti-inflammatory and pro-apoptotic properties (Elmali et al, 2007; Imler Jr and Petro, 2009; Sánchez-Fidalgo et al, 2010; Lee et al, 2011; Nakayama et al, 2012; Xuzhu et al, 2012).…”
Section: The Sirt1 Activator Resveratrol In Ra Therapymentioning
confidence: 99%